A comprehensive cost-benefit analysis of the penetration of Smart Grid technologies in the Saudi Arabian electricity infrastructure. (October 2019) - Alaqeel, T.A.; Suryanarayanan, S.
Abstract: The study proposes an economic framework based on detailed cost-benefit analysis of the insertion of Smart Grid technologies for electricity infrastructure modernization. The framework maps Smart Grid assets to their functions and benefits to estimate the feasibility of each Smart Grid technology and infrastructure. Net present value and discounted cash flow models, benefit/cost ratio, and minimum total cost are included in the analysis. The framework is applied to the Saudi electricity infrastructure as a case study. The framework is a comprehensive approach for economic analysis adapted from the EPRI Smart Grid model, the NETL modern grid initiative, and a study conducted by CESI and A.T. Kearney to estimate the impact of smart meters and smart equipment on the Saudi electric grid. Our findings show that advanced asset management infrastructure technologies are the most profitable technologies for the Saudi electricity infrastructure, followed by advanced distribution operations technologies, advanced transmission operations technologies, and advanced metering infrastructure technologies. Highlights: Cost-benefit economic analysis performed for modernizing the Saudi electricity infrastructure. A comprehensive economic framework for prioritized insertion of Smart Grid technologies is developed. Net present value, benefit/cost ratio, and total minimum cost are estimated for each Smart Grid technology. Advanced asset management technologies are the most profitable technologies to the Saudi electricity infrastructure.